Hemoglobin S and C Heterozygosity Enhances Neither the Magnitude nor Breadth of Antibody Responses to a Diverse Array of Plasmodium falciparum Antigens - Tan, Xiaolin (Oxford University Press, 2011)
(See the editorial commentary by Williams, on pages 1651–3.) Background. Heterozygous states of hemoglobin (Hb) A and HbS (HbAS, sickle-cell trait) or HbC (HbAC) protect against Plasmodium falciparum malaria by unclear mechanisms. Several studies suggest that HbAS and HbAC accelerate the acquisition of immunity to malaria, possibly by enhancing P. falciparum–specific antibody responses. Methods. We used a protein microarray representing 491 P. falciparum proteins expressed during exoerythrocytic and erythrocytic stages of the life cycle to test the hypothesis that HbAS and HbAC enhance the P. falciparum–specific IgG response compared with normal HbAA. Plasma samples were collected from Malian children aged 2–10 years before and after a 6-month malaria season and were probed against the microarray. Immunoglobulin G (IgG) profiles of children with HbAA (n = 106), HbAS (n = 15), and HbAC (n = 20) were compared. Results. Although the magnitude and breadth of P. falciparum–specific IgG responses increased with age and from before to after the malaria season in each antigen category, Hb type did not independently predict significant differences in P. falciparum–specific IgG profiles. Conclusions. These data do not support the hypothesis that HbAS and HbAC protect against malaria by enhancing P. falciparum–specific antibody responses. It remains possible that HbAS and HbAC protect against malaria by enhancing antibody responses to antigens not studied here or through other immune mechanisms.